Can Voluntary Adult Education Reduce Unemployment? Causal Evidence from East Germany after Reunification - Li Kathrin Kaja Rupieper; Stephan L. Thomsen (Institute of Labor Economics (IZA), 2024)
After the German Reunification in 1990, East Germany transitioned from a centrally planned economic system to a market economy. At the time, upskilling through adult education was deemed essential for the successful integration of the workforce into the labor market. Besides substantial mandatory training programs provided by active labor market policies, Volkshochschulen (VHS) were the most important providers of voluntary adult education. The economic effects of their courses have not been analyzed so far. Based on newly digitized data, we evaluate the effects of VHS courses on unemployment in a county-level analysis of East Germany between 1991 and 2002. Our identification strategy is based on a decentralized expansion of courses, which led to substantial and quasi-random variation in course numbers. We find no evidence that VHS courses harmed labor market integrations, in contrast to some active labor market policies. Courses did not affect subsequent unemployment on average. Yet, in counties neighboring West Germany, we find that courses reduced unemployment. Low labor demand may have restricted the realization of education effects. As both work-related and purely recreational courses reduced unemployment in counties bordering West Germany, our results also hint towards the relevance of social capital for successful labor market integrations.
Keywords: I21; J24; N34; P20; P36; 330; unemployment; adult education; non-formal education; Volkshochschule; East Germany